Investigating Students’ Anxiety Factors in Learning English at Junior High School - Nadia Murtaza; Meristika Moetia (Universitas Islam Negeri Palopo, 2026)
The purposes of this study were to find out the level of students’ anxiety in learning English at SMP N 1 Aceh Barat Daya and to describe its factors. The type of this research is descriptive qualitative research. The sample was 30 students of class VIII C and selected by using a random technique. There were two techniques of data collection: a questionnaire and an interview. The result of this study showed that 14 of the students (46,89%) had high anxiety, 11 of the students (37,5%) had middle anxiety, and five of the students (15.63%) were categorized as experiencing low anxiety. In addition, factors that contributed to students’ anxiety in learning English were a lack of confidence, fear of making mistakes, and fear of being judged. Students often doubt their ability to use English correctly, feel scared of saying the wrong thing, and worry about their errors.